2012
DOI: 10.1002/elan.201200245
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon Nanotube‐CaCO3 Nanoparticle Composites for the Construction of a Tyrosinase‐Based Amperometric Dopamine Biosensor

Abstract: We report the fabrication of a highly sensitive dopamine biosensor based on the entrapment of tyrosinase into CaCO3 nanoparticles at Multiwalled Carbon Nanotube (MWCNT) electrodes. CaCO3 acts as host matrix for tyrosinase and MWCNT provides a highly porous conductive network enhancing the enzyme immobilization and the electrochemical transduction of the enzyme reaction by boosting the amplification phenomenon involved in the biosensing of catechol and dopamine. The comparison of the performance of CaCO3‐tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…On the basis of previous investigations, we think that the replacement of gaseous CO 2 and H 2 with solid alkaline carbonates and MHs to achieve CO 2 methanation and the synthesis of CO x ‐free hydrogen/methane fuel mixtures have many inherent advantages. First, alkaline carbonates, especially for CaCO 3 , are abundant, inexpensive, safe, and easy to handle . Second, metal carbonate–MH systems are better suited for fuel storage and in situ fuel preparation as they are easy to store and transport and have a high volumetric energy density.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous investigations, we think that the replacement of gaseous CO 2 and H 2 with solid alkaline carbonates and MHs to achieve CO 2 methanation and the synthesis of CO x ‐free hydrogen/methane fuel mixtures have many inherent advantages. First, alkaline carbonates, especially for CaCO 3 , are abundant, inexpensive, safe, and easy to handle . Second, metal carbonate–MH systems are better suited for fuel storage and in situ fuel preparation as they are easy to store and transport and have a high volumetric energy density.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that tyrosinase was also electrodeposited on two to ten layers of poly-[β-CD-pyrrole/RGO], but these electrodes did not show any biosensing performance enhancement. This effect can be attributed to the steric hindrances induced by thick electropolymerized films towards the permeation of both substrate and oxygen, despite the higher electroactive area [15]. sensing where sensitivity and LOD were improved at these graphene-based electrodes.…”
Section: Resultsmentioning
confidence: 98%
“…We and others have recently demonstrated that three-dimensional bio-functionalized architectures enhance biosensing performances [15]. In particular, the use of carbon nanotube supports provides a combination of high electroactive area, high stability and high conductivity [16,17].…”
Section: Page 4 Of 18mentioning
confidence: 99%
“…Hence, numerous sensor applications for dopamine apply glassy carbon, screen-printed carbon or carbon paste electrodes. [25,26] A further increase of sensitivity of this kind of electrodes can be achieved by decoration of the electrode surface with nanomaterials such as carbon nanotubes, [27,28] nanocrystals, [29] graphene [30] or metal nanoparticles. [31] However, these carbon derived electrode materials show also some drawbacks for the detection of catecholamines.…”
Section: Introductionmentioning
confidence: 99%